WEB-BASED ONLINE LEARNING PLATFORM WITH RAD AND LARAVEL METHODS - Fahlevi, Mohammad Reza; Mu'minin, Saeful (ULTIMATICS, 2025)
Technological advancement has brought a great impact in the world of education, especially through utilizing e-learning technology to improve student learning outcomes. The e-learning system designed using the Laravel framework aims to provide easy and flexible access to learning materials as well as allowing class selection according to user needs. This research uses the Rapid Application Development (RAD) method to accelerate the e-learning system development process with a shorter and more efficient cycle. RAD methodology includes requirements planning, system design using UML, development with user feedback, and system implementation with black box testing and user acceptance testing. The implementation results include the login, dashboard, home, payment, class access, exam, and certificate pages. By using the RAD method, it is expected that this e-learning system can improve the learning experience of students at Universitas Nahdlatul Ulama Indonesia (UNUSIA) and provide an effective solution for limited access to learning materials. In addition, this system is expected to facilitate a more interactive and adaptive learning process, and support the achievement of more optimal academic results in this digital era.